2007
DOI: 10.1128/jvi.02433-06
|View full text |Cite
|
Sign up to set email alerts
|

Ebola Virus Glycoprotein 1: Identification of Residues Important for Binding and Postbinding Events

Abstract: The filoviruses Ebola virus (EBOV) and Marburg virus (MARV) are responsible for devastating hemorrhagic fever outbreaks. No therapies are available against these viruses. An understanding of filoviral glycoprotein 1 (GP1) residues involved in entry events would facilitate the development of antivirals. Towards this end, we performed alanine scanning mutagenesis on selected residues in the amino terminus of GP1. Mutant GPs were evaluated for their incorporation onto feline immunodeficiency virus (FIV) particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
116
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(123 citation statements)
references
References 36 publications
(59 reference statements)
7
116
0
Order By: Relevance
“…Previous work has shown that many residues throughout GP 1 are important for EBOV GP 1,2 -mediated entry into host cells (3,15,17), but to date there have been no direct binding studies with mutant GP 1,2 proteins. Since the smallest RBR we analyzed (RBR-7; GP 1 residues 90 to 149) bound specifically to permissive cells, we engineered Ala substitutions (into RBR-1-Fc) at each residue between residues 90 and 149 that had been suggested to be important for receptor binding (based on infectivity studies) and that did not compromise GP 1,2 incorporation into pseudovirions: these were K95, K114/K115, K140, and G143 (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work has shown that many residues throughout GP 1 are important for EBOV GP 1,2 -mediated entry into host cells (3,15,17), but to date there have been no direct binding studies with mutant GP 1,2 proteins. Since the smallest RBR we analyzed (RBR-7; GP 1 residues 90 to 149) bound specifically to permissive cells, we engineered Ala substitutions (into RBR-1-Fc) at each residue between residues 90 and 149 that had been suggested to be important for receptor binding (based on infectivity studies) and that did not compromise GP 1,2 incorporation into pseudovirions: these were K95, K114/K115, K140, and G143 (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since the smallest RBR we analyzed (RBR-7; GP 1 residues 90 to 149) bound specifically to permissive cells, we engineered Ala substitutions (into RBR-1-Fc) at each residue between residues 90 and 149 that had been suggested to be important for receptor binding (based on infectivity studies) and that did not compromise GP 1,2 incorporation into pseudovirions: these were K95, K114/K115, K140, and G143 (see Fig. S2 in the supplemental material) (3,15,17). We also created three mutants with composite mutations, which we denoted 3mer (K114A/K115A/K140A), 4mer (K95A/K114A/K115A/K140A), and 5mer (K95A/K114A/ K115A/K140A/G143A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasmids expressing adeno-associated virus 2 encoding luciferase (AAV2-luciferase) and AAV2-nuclear green fluorescent protein (GFP) were supplied within the laboratory. All plasmids used to generate feline immunodeficiency virus (FIV) and VSV core pseudovirions have been previously described (3,42). All plasmids used to generate HIV and murine leukemia virus (MuLV) core pseudovirions are commercially available from Invitrogen and Clontech, respectively.…”
Section: Cell Linesmentioning
confidence: 99%